COMPLEMENTARY NURSING COMMUNITY SERVICE OF STIKES BULELENG, POLTEKKES DENPASAR, AND UNIVERSITY OF FORT DE KOCK BUKITTINGGI IN KLUNGKUNG, BALI - I Wayan Antarikswan; I Made Sundayana; I Dewa Ayu Rismayanti; Gede Budi Widiarta; Made Yos Kresnayana; Gede Ivan Kresnayana; Ni Made Dwi Yunica Astriani; Ni Putu Indah Sintya Dewi; Mochamad Heri; G. Nur Widya Putra; I Kadek Yudi Aryawan; Aditha Angga Pratama; Made Martini; Agus Ari Pratama; Ni Ketut Putri Marthasari; Putu Wahyu Sri Juniantari Sandy; Ni Luh Linda Ayuni Tania; Ni Putu Diah Ayu Rusmeni; Luh Seri Astuti; I Wayan Suardana; Yelmi Reni Puteri (Jurnal Pengabdian Masyarakat Sundaram, 2025)
High blood pressure, better known as hypertension, is now a global health problem of increasing concern. This disease is included in the list of the ten leading causes of death worldwide, and each year claims many lives. Therefore, effective prevention and treatment measures are urgently needed to address hypertension worldwide. A preliminary study conducted in Dawan Village revealed 60 cases of hypertension in the past six months. Based on these initial findings, researchers were motivated to conduct further research on how wet cupping therapy can help lower cholesterol levels and blood pressure in hypertensive patients in Dawan Village. This initiative was welcomed by the residents of Dawan Kaler Village, located in Klungkung Regency, Bali Province. The goal is to provide the Dawan Kaler community with sufficient knowledge on how to manage hypertension and control their cholesterol levels. This community service program is expected to increase awareness and understanding of hypertension among Dawan Kaler residents, as well as the benefits of cupping therapy in lowering blood pressure and cholesterol.